Seismic and hydromechanical performance of rammed earth walls under changing environmental conditions. (20th September 2021) - Villacreses, Juan P.; Granados, Jaime; Caicedo, Bernardo; Torres-Rodas, Pablo; Yépez, Fabricio
Highlights: Environmental effects on rammed earth walls performance. The effect of the material's suction on earth structures. A novel procedure to study structure-environmental interaction and mechanical behavior. An application of the rheometer and climatic chamber to study structures made using compacted soils. Abstract: Rammed earth walls are influenced by suction (a function of the water content) which varies depending on environmental conditions. The influence of climate on walls' performance under seismic movements was studied in two wall's geometries (2.5*2.4*0.3 m and 2.5*2.4*0.5 m). First, the soil's mechanical properties were determined for different suction pressures; afterward, the soil-environment interaction flux was measured using a climatic chamber. Then, numerical models were used to simulate the water profiles within the structure and its seismic performance. A markedly different behavior was observed according to the hydric state of the walls that depends on the hydraulic gradient in the cross-section of the wall. The results obtained in this investigation found higher relative accelerations for walls in the wet state compared to the dry state (84% higher). These results open up new possibilities to study the structure-environment interaction and its influence on the mechanical behavior of rammed earth structures.